Neutron diffraction study of antibacterial bioactive calcium silicate sol‐gel glasses containing silver. (12th September 2017) - Carta, Daniela; Jones, Julian R.; Lin, Sen; Poologasundarampillai, Gowsihan; Newport, Robert J.; Pickup, David M.
Abstract: Bioactive sol‐gel calcia‐silica glasses can regenerate damaged or diseased bones due to their ability to stimulate bone growth. This capability is related to the formation of a hydroxyapatite layer on the glass surface, which bonds with bone, and the release of soluble silica and calcium ions in the body fluid which accelerates bone growth. The addition of silver ions imbues the glass with antibacterial properties due to the release of antibacterial Ag + ion. The antibacterial activity is therefore closely dependent on the dissolution properties of the glasses which in turn are related to their atomic‐level structure. Structural characterization of the glasses at the atomic level is therefore essential in order to investigate and control the antibacterial properties of the glass. We have used neutron diffraction to investigate the structure of silver‐containing calcia‐silica sol‐gel bioactive glasses with different Ag2 O loading (0, 2, 4, 6 mol%). The presence of the silver had little effect on the host glass structure, although some silver metal nanoparticles were present. Results agreed with previous computer simulations.